Paradox of circulating advanced glycation end product concentrations in patients with congestive heart failure and after heart transplantation. Issue 11 (14th October 2004) - Heidland, A; Šebeková, K; Frangiosa, A; De Santo, L S; Cirillo, M; Rossi, F; Cotrufo, M; Perna, A; Klassen, A; Schinzel, R; De Santo, N G
Abstract : Objectives: To analyse circulating concentrations of advanced glycation end products (AGEs) in patients with severe congestive heart failure (CHF) and after heart transplantation; to identify the potential contribution of kidney function to plasma AGE concentrations; and to determine whether AGE concentrations and parameters of oxidative stress are interrelated. Methods and results: Circulating N ε -(carboxymethyl)lysine (CML) and AGE associated fluorescence (AGE-Fl), lipid peroxidation, and glomerular filtration rate (GFR) were measured in a cross sectional study of 22 patients with advanced CHF, 30 heart transplant recipients, and 20 healthy controls. Compared with the controls, the CHF patients had decreased CML (mean (SEM) 467.8 (20.0) ng/ml v 369.3 (22.3) ng/ml, p < 0.01), AGE-Fl (mean (SEM) 302.2 (13.3) arbitrary units v 204.9 (15.7) arbitrary units, p < 0.01), and GFR (p < 0.01). CML was positively related to decreased total protein and serum albumin and negatively to body mass index (p < 0.01). In contrast, in the heart transplant group, impaired GFR was associated with a notable rise of both CML (mean (SEM) 876.1 (53.1) ng/ml, p < 0.01) and AGE-Fl (mean (SEM) 385.6 (26.1) arbitrary units, p < 0.01). A positive relation between CML and serum albumin ( r = 0.394, p < 0.05) and lipofuscin ( r = 0.651, p < 0.01) was found. Conclusions: The contrasting concentration of CML and AGE-Fl between patients with CHF and after heart transplantation in the presence of decreased GFR and oxidative stress are explained by lowered plasma proteins in CHF and higher concentrations in heart transplant recipients. In heart transplant recipients, in addition to myocardial inflammatory processes, immunosuppression may be important for enhanced formation of AGEs.